Deciphering the Relationship between Salivary Cortisol Levels and Hypertension Using Enzyme-linked Immunosorbent Assay - An Observational Study - Sathiyamoorthy, Mounika; Divya, Bose; Ramadoss, Ramya; Dineshkumar, Thayalan; Narayan, Madhu; Vasanthi, V.; Rameshkumar, Annasamy; Rajkumar, Krishnan (Journal of Nature and Science of Medicine, 2024)
Abstract Background: Cortisol plays a major role in stress crises and is higher among patients with hypertension. Assessment of cortisol levels can serve as a predictor for the prevention of complications of hypertension. Aim: The study aimed to investigate the relationship between salivary cortisol levels and hypertension. Materials and Methods: Twenty hypertensive individuals (Group I) and 20 control subjects (Group II) participated in the study. Their blood pressure was measured, followed by the collection of morning and evening saliva samples. Salivary cortisol levels were estimated using an enzyme-linked immunosorbent assay kit. Unpaired Student's t-test and Pearson's correlation coefficient were done to statistically analyze the data using SPSS statistical analysis software. Results: Group I had mean morning cortisol levels that were higher (0.376-0.458 g/dL) than those in Group II (0.005-0.0001 g/dL). In Group I participants, there was a positive correlation between evening cortisol levels and pulse pressure (P = 0.05). Conclusion: In this study, we found high cortisol levels in patients with hypertension. Increased salivary cortisol levels could be an indicator of underlying cardiovascular complications.